DAMPAK PENGGUNAAN AI CHATGPT DALAM PEMBELAJARAN DI KALANGAN MAHASISWA PGSD UNIVERSITAS RIAU - Elfi Anisa; Maria Ulfa; Mitha Dwi Anggriani (CV. Adiba Aisha Amira, 2025)
This study aims to analyze the impact of the use of Artificial Intelligence (AI) ChatGPT in the learning process among students of the Primary School Teacher Education Study Program (PGSD) at the University of Riau. The research method used is a quantitative method with a survey approach. The research sample consisted of 30 students selected using purposive sampling. The research instrument was a closed-ended questionnaire with a Likert scale to measure students' perceptions of the effectiveness, ease, and relevance of using ChatGPT in supporting learning. The data obtained was analyzed using quantitative descriptive analysis techniques. The results of the study showed that the use of ChatGPT had a positive impact on improving material comprehension, learning motivation, and efficiency in searching for information. Additionally, there is a significant relationship between the intensity of ChatGPT usage and student learning outcomes. The results of this study provide a basis for universities to design policies for the wise use of ChatGPT in learning, so that AI technology can be optimally utilized to improve digital literacy, critical thinking skills, and professionalism among students as future teachers.